الحملات الإعلانية الرقمية لهواتف آيفون وتأثيرها على السلوك الشرائي للشباب الأردني - الخصاونة، إبراهيم فؤاد (اتحاد الجامعات العربية - الجمعية العلمية لكليات الآداب, 2023)
تتناول الدراسة دور الإعلان في زيادة الثقافة الشرائية لأفراد المجتمع من خلال توضيح مزايا المنتجات عندما تتركز فكرة الإعلان الأساسية على جذب انتباه المستهلك، فبعد التحولات التكنولوجية والمعرفية المتسارعة التي شهدها العالم في ظل الجيل الخامس من الإنترنت والذكاء الاصطناعي الذي أحدث طفرة نوعية في تسويق الإعلانات، وساعد في انتشارها عالميا، أصبح الإعلان أداة تغيير وتأثير فاعلة على العمليات التجارية المختلفة، لأنه من وسائل الاتصال التي تعنى بالتأثير على المستهلك. هدفت الدراسة التعرف إلى تأثير الحملات الإعلانية الرقمية لهواتف آيفون العالمية iphone على السلوك الشرائي للشباب الأردني، ومعرفة الأساليب الفنية لحملاتها الإعلانية الرقمية، والمؤثرات النفسية التي تستخدمها للتأثير على السلوك الشرائي للشباب. اعتمد الباحث المنهج الوصفي التحليلي لتوضيح تأثير الحملات الإعلانية الرقمية لهواتف آيفون، وهي دراسة وصفية، استخدمت منهج المسح، والاستبانة أداة لجمع البيانات والمعلومات من عينة عشوائية لفئة الشباب في محافظة إربد بلغت 744 مفردة. وخلصت نتائج الدراسة إلى أن أهم مصادر إعلانات آيفون، هي إعلانات الهواتف على مواقع شبكة الإنترنت، وهذا يشير إلى أن الشركة تواكب المستجدات العالمية، وتحاول جذب الشباب في إعلاناتها للتعريف بإصداراتها الجديدة في السوق، ومعرفة أسعارها واختصار الوقت في تبسيط عملية شرائها من الخارج قبل وصولها إلى الأردن. وتحاول الشركة المنتجة لهواتف آيفون إظهار أهم ميزات هواتفها الجديدة للترويج لشرائها، مراعية المصداقية فيما تعلنه، وكان التصميم الجاذب للإعلان من أكثر العوامل جذبا للشباب بما اشتمل عليه من صوت وصورة وألوان، ووفر معلومات ذات أهمية. وأوصت الدراسة بضرورة الأخذ بردود فعل المستهلكين حيال الإعلان عن المنتج لمعرفة ما يواجههم من معوقات أثناء الشراء، والاهتمام بتطوير الإعلانات الرقمية لشركة آيفون بغية الوصول إلى فئات عمرية مختلفة، والتأكيد على إجراء بحوث تتابعية مستمرة لمعرفة آراء مختلف المستهلكين، وضرورة عمل استبانة تحدث باستمرار من قبل شركة هواتف آيفون موجهة لزبائنها المعرفة ردود فعلهم حول الميزات التي تحملها الهواتف الجديدة ودرجة توافقها مع الإعلانات. The study deals with the role of advertising in increasing the purchasing culture of members of society by explaining the advantages of products when the basic idea of advertising is focused on attracting the attention of the consumer, after the rapid technological and cognitive transformations that the world witnessed in light of the fifth generation of the Internet and artificial intelligence, which made a quantum leap in advertising marketing, And it helped spread it globally, as advertising became a tool for change and effective influence on various business operations, because it is one of the means of communication that deals with influencing the consumer. The study aimed to identify the impact of the digital advertising campaigns of the international company iPhone, on the purchasing behavior of Jordanian youth, and to know the technical methods of its digital advertising campaigns, and the psychological effects that it uses to influence the purchasing behavior of young people. The researcher adopted the descriptive analytical approach to clarify the impact of the company’s digital advertising campaigns. It is a descriptive study that used the survey method and the questionnaire as a tool for collecting data and information from a random sample of young people in Irbid governorate, which amounted to 744 individuals. The results of the study concluded that the most important sources of iPhone advertisements are phone advertisements on the Internet, and this indicates that the company keeps pace with global developments, and tries to attract young people in its advertisements to introduce its new releases in the market, know its prices, shorten the time and ease of purchasing it from abroad before arriving in Jordan. The company that produces iPhone phones is trying to show the most important features of its new phones to promote its purchase. And that the attractive design of the advertisement was one of the most attractive factors for young people, as it contained sound, image and colors, and provided important information. The study recommended the need to take into account the reactions of consumers regarding the advertisement of the product to know the obstacles that direct them during the purchase, and to pay attention to the development of digital advertisements for iPhone in order to reach different age groups. Emphasis on conducting continuous sequential research to find out the opinions of different consumers. And the necessity of making a constantly updated questionnaire by iPhone phones directed at its customers to find out their reactions about the features that the new phones carry and the degree of their compatibility with ads.
Keywords: التسويق الإلكتروني -- الإعلانات الرقمية -- الثقافة الشرائية -- هواتف أبل -- الشباب الأردني